Exploring the Effectiveness of International Knowledge Cooperation - Klingebiel, Stephan. author. aut Link
XXIII, 161 p. 15 illus., 14 illus. in color.
Keywords: “This book is a pioneering attempt to systematically and concretely analyze diverse knowledge actors, focusing on a typology of their modalities of knowledge interaction. Highly recommended for researchers, policy makers, and practitioners interested in shaping the future of knowledge partnerships.” ---Izumi Ohno, Professor, National Graduate Institute for Policy Studies (GRIPS), Japan "The authors in this timely and very accessible book, leaning on a wealth of experiences across the world, expose the diverse modalities of knowledge production and exchange which already occur and probably should occur in the realm of interactions we call 'development'. They emphasize the need for co-production of knowledge, while wisely refraining from replacing one form of modernism by new high-modernist state building projects and their models of knowledge for development." ---Kristof Van Assche, Professor Planning, Governance & Development, Universityof Alberta, Canada In this open access book, we provide evidence to support the conceptual discussion of what constitutes “modalities of knowledge interaction” and suggest an analytical framework for effective knowledge cooperation. In practice, knowledge cooperation is realised through different modalities that serve as a toolbox to co-create, share and communicate knowledge among actors. Effective knowledge cooperation is crucial to addressing global challenges. It is increasingly attracting attention due to the rise of South–South Cooperation, to which it is central. Our empirical cases (Germany, India, Republic of Korea and Rwanda) comprise South-South cooperation and traditional development cooperation actors. Dr Stephan Klingebiel is Head of the Research Programme “Inter- and Transnational Cooperation” at the German Institute of Development and Sustainability (IDOS) and Visiting Professor at Ewha Womans University (Graduate School of InternationalStudies), Seoul. Flora L. Hartmann graduated from the M.Sc. Geography of Environmental Risks and Human Security at the United Nations University (UNU-EHS). Elisa Madani studied International Management at the Hochschule für Wirtschaft und Recht in Berlin and the Ecole Supérieure du Commerce Extérieur in Paris. Jonas Paintner studied Global Political Economy as well as International Development and was part of the Postgraduate Research Programme at IDOS. Rebekka A. Rohe studied International Relations (MA) at the Freie Universität Berlin, the Humboldt-Universität zu Berlin, Potsdam University, and the Hebrew University of Jerusalem. Lisa Trebs studied Development Studies at the Institute of Development Studies, UK. Teodor Wolk has an academic background in human- and economic geography.